THE CONCEPT OF SCIENTIFIC BASES OF PROFESSIONAL ENGINEERS IN THE FIELD OF ENVIRONMENTAL - Olga Andreevna Linenko (Вестник Северо-Кавказского федерального университета)
The carried out theoretical analysis of the engineering activities allow to complement the concept of scientific fundamentals of professional activity of engineers in the sphere of nature.